Pengaruh Penambahan Fruktosa dalam Pengencer Natrium Klorida Fisiologis Kuning Telur Ayam Ras terhadap Kualitas Spermatozoa Babi Landrace - Toto, Novaldy Imanuel; Nalley, Wilmientje M.; Marawali, Aloysius; Mata Hine , Thomas (Yayasan Sumber Daya Manusia Cerdas, 2024)
This study aims to determine the effect of adding fructose to egg yolk diluent on the quality of Landrace pig spermatozoa. This research used a completely randomized design (CRD) method with 6 treatments and 5 replications. The following are the various treatments, namely: T0=NaCl fis 2.4 mL + TY 0.6 grams + 0 grams of fructose, T1= NaCl fis 2.4 mL + TY 0.6 grams + 0.015 grams of fructose, T2= NaCl fis 2 .4 mL + TY 0.6 gram + 0.030 gram fructose, T3= NaCl fis 2.4 mL + TY 0.6 gram + 0.045 gram fructose, T4= NaCl fis 2.4 mL + TY 0.6 gram + 0.060 gram fructose, and T5 = NaCl fis 2.4 mL + TY 0.6 grams + 0.075 grams of fructose. Good quality cement is diluted using treatment diluent, evaluated post-dilution, packaged in ependop then stored in a cool box with a temperature of 18-20°C. Evaluation of spermatozoa motility, viability, abnormalities and survival is carried out every 8 hours. The research results obtained showed that the 24th hour of storage with treatment T0 (47.00 ± 10.95), T1 (51.00 ± 7.42), T2 (55.00 ± 6.12), T3 (54.00 ±4.18), T4 (50.00±3.54), and T5 (44.00±4.18) were able to stay above 40% which is feasible for IB. Statistical tests showed that the treatments did not significantly differ on the quality of landrace pig spermatozoa. It was concluded that the semen quality of landrace pigs could be optimally improved by using a fructose level in the diluent of 0.30 grams.